(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the concept of the letter, one of the main categories of Arabic grammar. In Arabic grammar, the concept of the letter is of great importance, and its definition, main characteristics, and types are analyzed based on the classical grammar source—Sibawayh’s "Al-Kitab"—and A. Abdujabborov’s textbook "The Arabic Language." At the same time, the comparative relationship of the category of letter in the Arabic language with auxiliary verbs and conjunctions in the Uzbek language is studied.